2019
DOI: 10.1186/s12885-019-5997-2
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel S6K1 inhibitor, rosmarinic acid methyl ester, for treating cisplatin-resistant cervical cancer

Abstract: Background The mTOR/S6K1 signaling pathway is often activated in cervical cancer, and thus considered a molecular target for cervical cancer therapies. Inhibiting mTOR is cytotoxic to cervical cancer cells and creates a synergistic anti-tumor effect with conventional chemotherapy agents. In this study, we identified a novel S6K1 inhibitor, rosmarinic acid methyl ester (RAME) for the use of therapeutic agent against cervical cancer. Methods Combined structure- and ligand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 60 publications
2
20
0
Order By: Relevance
“…Here, we report that beetroot and leaf extracts did not activate the Akt feedback loop even though they efficiently inhibited the mTOR pathway. Nam et al (2019) demonstrated that inhibition of S6K1 in cervical cancer cells enhanced the PARP1 cleavage as reported here with the treatment with leaf and root extract. In accordance with our findings, the inhibition of S6K1 in TE8 esophageal cancer cells also led to the downregulation of cyclin D (S.-H. Kim, Jang, Chau, Pyo, & Um, 2013).…”
Section: Discussionsupporting
confidence: 81%
“…Here, we report that beetroot and leaf extracts did not activate the Akt feedback loop even though they efficiently inhibited the mTOR pathway. Nam et al (2019) demonstrated that inhibition of S6K1 in cervical cancer cells enhanced the PARP1 cleavage as reported here with the treatment with leaf and root extract. In accordance with our findings, the inhibition of S6K1 in TE8 esophageal cancer cells also led to the downregulation of cyclin D (S.-H. Kim, Jang, Chau, Pyo, & Um, 2013).…”
Section: Discussionsupporting
confidence: 81%
“…Previously, it was reported that RAME induced the autophagy and apoptosis of cervical cancer cells [ 20 ]. To further elucidate the molecular pathways demonstrating its anti-tumor effects against ovarian cancer, we performed the RNA-sequencing of RAME-treated SKOV-3 ovarian cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…To further elucidate the molecular pathways demonstrating its anti-tumor effects against ovarian cancer, we performed the RNA-sequencing of RAME-treated SKOV-3 ovarian cancer cells. Since 40 µM of RAME treatment showed apoptotic effects in cervical cancer cells [ 20 ], we treated another ovarian cancer cell line, SKOV-3, with 40 µM of RAME. As shown by the RNA-sequencing data, 2789 differentially expressed genes (DEGs) were identified, including 1337 upregulated genes and 1452 downregulated genes ( Figure 1 A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4C). Rapamycin analogs ("rapalogs") are in clinical use against human cancer and act in part by inhibiting S6K (Ferrari, et al 1993, Meng andZheng 2015), and S6K inhibitors are under development as cancer therapeutics (Nam, et al 2019, Pearce, et al 2010, consistent with a wellestablished role of S6K activation in the molecular pathogenesis of multiple cancers.…”
Section: Efficacy Of Ta/dda Mono-and Combination Anti-cancer Therapymentioning
confidence: 99%